(untitled) (Global Journal of Science Frontier Research, 2014)
A field study was undertaken to optimize the planting time for different soybean cultivars in agro-ecological conditions of Faisalabad, Punjab. The experiment was comprised of planting times (21st January, 28th January, 4 th February, 11th February and 18th February) and two cultivars (SA 72-60 and Faisal soybean). Replicated three times, the experiment was laid out in randomized complete block design with split plot arrangement having planting time in main-plot and cultivar in subplot. Data were collected on number of pods per plant, number seeds per plant, plant height, 1000-seed weight, seed yield, biological yield, protein percent and oil percent. Statistical analysis of data revealed significant differences among means of traits at different planting date treatments. Cultivars with early planting produced higher yield and quality as compared to the late planting dates. The results revealed that higher numbers of pods per plant and number of seeds per plant were produced by 28th January and Faisal soybean. Similarly maximum seed yield (1647.10 kg ha-1 and 1440.23 kg ha-1) were also produced by 28th January, Faisal soybean and 21st January, Faisal soybean, respectively. Thus 28th January planting was the best for high yield of spring soybean. While, among two cultivars Faisal soybean performed the best in Faisalabad.